Searching of Conserved Motifs within a Partial secA Gene Sequence of Phytoplasma Associated with Root (Wilt) Disease of Coconut (Cocos nucifera) in India: Using a Frequency Based Approach - Shil, Sandip; Das, Kishore K.; Dutta, Anamika (International Journal of Bio-resource and Stress Management, 2015)
Coconut palm (Cocos nucifera L.) root (wilt) disease (CRWD) became a serious concern for coconut cultivation in coastal region of India. Due to which, India looses a considerable economic loss of about 968 million nuts, annually. The disease is non lethal. It has already been reported that species of the phytoplasmas, belonging to ribosomal group 16SrXI, are primarily associated with CRWD. In the current study, our objective is to identify motif that describes the conserved region within protein sequence of CRWD. Due to variations of amino acid residues at given positions within a positional weight matrix (PWM), the pattern of protein sequence motif can be identified using a multinomial probabilistic model. The basic assumption underlying this model is that the amino acid residues within a sequence are independent and identically distributed. To determine the overall probability of that PWM, the formula for computing information content or relative entropy may also be used. Here, such measure has been proposed to identify motifs within PWM, in this paper. Finally, various conserved motifs within the partial secA gene sequence of phytoplasma associated with CRWD, using that measure, have been successfully identified. On the basis of obtained results, we reached to conclusions that conserved regions or motifs (of different length) are expected to be found at (163-171) and (120-138) positions of within that partial secA gene sequence.